PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA MENJADI POC (PUPUK ORGANIK CAIR) DI DESA SUNGAI BAKAR KECAMATAN BAJUIN - Zulipah Mahdalena; Muhammad Rifky Aditya (Fakultas Pertanian UVAYA Banjarmasin, 2025)
The issue of waste has generally become a classic problem that is dificul to solve. The rise in public consumption to satisfy their living needs is a contributing factor to the waste issue. Household organic waste is one of the contributing causes to the waste problem that be transported to the final disposalsite (TPA). Organic waste, due to its easily rotting nature, can produce an unpleasant odor and also attract many flies which cause disease. Sungai Bakar villiges in bajuin district, Tanah Laut Regency, South Kalimantan Province,and is the gateway to the Bajuin waterfall tourist attraction. The distance of Sungai Bakar village is 10 km from pelaihari city and 75 km from Banjarmasin city. Becaause most of the people of Sungai Bakar village are farmers and work in Agriculture, it is deemed necessary to provide information on the manufacture of liquid organic fertilizer (POC). Liquid organic fertilizer is made by utilizing household organic waste as an alternative to reducing waste problems. The purpose of this community service is to increase the knowledge, insight and independence of the community in managing organic waste. This community service activity was carried out in Sungai Bakar village, Bajuin district, Tanah Laut regency, held on May 19 - 20, 2025. This community service activity was attended by the community service team from the Agribusiness study program and the Aquaculture study program, Sungai Bakar village officials, and the local village community. The approach method used is the lecture method, demonstration , discussiob and question and answer. The stages of activities and evaluation. Some solutions that can be applied to reduce pollution due to household organic waste in Sungai Bakar village are : 1. Socialization or counseling about the economic value of waste 2. Sorting and separating waste based on its category, namely organic waste and an organic waste. 3. Making liquid organic fertilizer from household organic waste. Community service activities regarding the management of household organic waste into liquid organic fertilizer in Sungai Bakar village have a positive impact on the community so that they can increase community knowledge,insight and independence